The importance of relationship quality in building effective Customer Relationship Management (CRM) at Perodua Manufacturing Sdn. Bhd. - Saleh, Siti Sarah (2007)
As the dynamics of customer relationship have change dramatically and forced to meet the new revolution of relationship building, organization need to manage customer relationship effectively to remain competitive. The importance of relationship quality is to optimize customer and partner satisfaction, revenue and business efficiency by building the strongest possible relationship at organization level. This research utilized a convenience methodology to measures relationship quality between the organization and its customers, and the researcher has helped the firm identifying the factors that contribute to relationship quality and its importance to build effective Customer Relationship Management (CRM). Four factors which contribute to relationship quality had been identified by researcher consist of trust, commitment, satisfaction and communication. The findings highlighted all the four factors does contributes to relationship quality and the firm should take actions and focuses more on these four contributions factors in order to effectively manage relationship with customers. The researcher also identified the strengths and weaknesses of each factors and came out with recommendations such as enhance commitment to build long-term relationship, establishing communication to improve relationship quality, enhancing trust in building effective working environment and increase satisfaction to build relationship quality and improve management efficiency. By implementing these four recommendations, the researcher optimism that it will help the firm to better upgrade its performance in any area that is not running well in the management for future use.